A Study of Knowledge, Attitude and Practice of Teaching Methods amongst First Year Medical Students in Anatomy in Government Medical Colleges of Gujarat: A Comparative Evaluation On Mandibular Movements - Shah, Hirendra R.; Shah, Shaival B. (National Journal of Integrated Research in Medicine, 2018)
Introduction: Admission to a particular institute cannot be considered as a measure of merit. In spite of hair split merits, in later stages of career, performances differ greatly from one student to another in same institution and the results of final exams differ from institution to institution. Apart from individual capacities to grasp and retain subject, something in teaching methods could be responsible for such diversity. Method: In view of above cited situation and to know the performance and evaluate the possible factors this modest study was formulated. A questionnaire was distributed amongst all willing students of all the Government medical colleges. Researchers explained about the need of anonymity in study. It was emphasized that they be honest and non-partial in answering all the questions. Discussion: This study brings out some salient features of current trends in teaching anatomy in government medical colleges of Gujarat. Conclusion: Planning of teaching methods should consider the reasonable and justifiable opinions of students. [Hirendra S NJIRM 2017; 8(4):99-102]